Health care utilization as a predictor of death anxiety in older adults. Issue 3 (16th March 2022) - Becker, Todd D.
Abstract: The relationship between health care utilization and death anxiety in older adults is underexplored. This secondary analysis of the 2012 Health and Retirement Study examined health care utilization as a predictor of death anxiety in a nationally representative sample of American older adults ( N  = 3, 960). Hierarchical binary logistic regression results revealed that overnight hospitalization, overnight nursing home placement, and outpatient visit were all statistically significant predictors of death anxiety. Outpatient visit was the strongest health care utilization predictor in the model. Increased end-of-life training for providers may improve patient–provider communication and alleviate patients' death anxiety. Future research should explore the directionality between study variables.